2015
DOI: 10.5430/jha.v4n6p21
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of burnout among physicians and advanced-practice clinicians in central New York

Abstract: Background: Provider wellbeing is a barometer of the strength of healthcare systems/organizations. Burnout prevalence among physicians exceeds that among other adult workers in the United States. Rural-based practitioners might be at greater risk. Objective: We investigated predictors of burnout among group-employed providers within an integrated healthcare network. Methods: In a prospective observational study of physicians/advanced-practice clinicians serving an 8-county region of central New York, we linked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…We demonstrated convergent validity of burnout screening measures by testing their correlations with workload and job dissatisfaction. We measured “perceived workload” on a five‐item scale described in a previous report (Waddimba et al, ). Constituent items inquire about patient load, leaving work undone, taking work home, exceeding one's fair share of workload, and neglecting health due to work, on a four‐point Likert‐style response format from 1 (“ Never [0% of the time]”) to 4 (“ Frequently [>75% of the time]”).…”
Section: Methodsmentioning
confidence: 99%
“…We demonstrated convergent validity of burnout screening measures by testing their correlations with workload and job dissatisfaction. We measured “perceived workload” on a five‐item scale described in a previous report (Waddimba et al, ). Constituent items inquire about patient load, leaving work undone, taking work home, exceeding one's fair share of workload, and neglecting health due to work, on a four‐point Likert‐style response format from 1 (“ Never [0% of the time]”) to 4 (“ Frequently [>75% of the time]”).…”
Section: Methodsmentioning
confidence: 99%
“…We conducted secondary analysis of cross‐sectional data from the Practitioner Resilience, Adaptability and Wellbeing Study (PRAWS) (Waddimba et al. ,b), a prospective observational study investigating a community of physicians and mid‐level practitioners of patient care within an integrated delivery system.…”
Section: Methodsmentioning
confidence: 99%
“…We assessed subjective workload quantity by a perceived workload scale specifically designed for the parent study, and described in a previous report (Waddimba et al. ). It comprises five items (e.g., I feel stressed out from having too much work ), each rated on a four‐point Likert‐style response format ranging from 1 = “ Never or 0 percent of the time” to 4 = “ Frequently or >75 percent of the time.” It was scored by summing up the items.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, lower career satisfaction was associated with insuffi cient resources for managing patients with complex clinical conditions [12]. Using cross-sectional data from the Practitioner Resilience, Adaptability and Wellbeing Study [41], Waddimba and colleagues evaluated burnout among rural clinicians in an integrated health care system in New York. Similar to Whitebird et al, researchers found that nearly a third of clinicians reported symptoms of burnout using the single-item PWS measure.…”
Section: Burnoutmentioning
confidence: 99%
“…Similar to Whitebird et al, researchers found that nearly a third of clinicians reported symptoms of burnout using the single-item PWS measure. Risk factors for burnout included employment in smaller clinics, lower tolerance of stress, more frequent dissatisfaction with practice, and unmet relationship needs [41].…”
Section: Burnoutmentioning
confidence: 99%